Diversity of functional trade‐offs enhances survival after fire in Neotropical savanna species. (13th November 2019) - Corrêa Scalon, Marina; Maia Chaves Bicalho Domingos, Fabricius; Jonatar Alves da Cruz, Wesley; Marimon Júnior, Ben Hur; Schwantes Marimon, Beatriz; Oliveras, Imma
Abstract: Questions: What are the trade‐offs and/or associated syndromes within and between fire‐associated traits? Does bud protection relate to bark properties and tree resprouting ability? Which traits will influence post‐fire tree survival (mortality rate and top‐kill) and tree recovery (canopy recovery and resprouting volume)? Do species with different leaf phenology have the same ecological strategies to survive and recover from fire? Location: Tree community in a Neotropical savanna. Methods: For each of the 24 most abundant species, we characterised the trade‐offs among bud protection, bark traits, mortality, canopy recovery and top‐kill, and resprouting strategies in both a burned and adjacent unburned area of Cerrado vegetation. Results: Species with unprotected buds had a higher risk of dying, while high bud protection was associated to the ability to resprout from both the canopy and the base of the tree. We found three major trade‐offs defined by bark traits and plant properties. Cerrado woody species invest in either (a) high inner bark thickness and bark moisture, or (b) fast growth rate, height and bark density, or (c) thick outer bark and high wood density with high bud protection. Conclusions: Cerrado species show different sets of fire‐related traits that seem to be important for both individual survival and community assembly. Here, we report these trade‐offs for Neotropical savannas, and our findings also shed light on how changes in fire regime may favour different groups of species, leading to changes in plant communities over time. Abstract : In the Brazilian Cerrado, trees have developed distinct strategies to survive and recover after fire, by differently investing in bark structural traits and growth. Low bud protection is associated with a higher mortality risk, while species with highly protected buds promptly recover, resprouting both from the canopy and the base.